RUANG KESADARAN DIALEKTIK, MAMPANG PRAPATAN, JAKARTA SELATAN - Angelita Permatasari Angkola; Alvin Hadiwono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Living in the middle of the hustle and bustle of urban modernization, a high city lifestyle, dense environmental conditions, and the demands of work make people feel psychological pressure, so that the risk of stress in urban areas increases. In addition, rapid technological advances make it easier for metropolitan citizen to get stressors (stressful situations). This makes it more difficult for individuals to deal with stress due to social, economic and environmental demands that continue to affect our surroundings. When the citizen often under prolonged stress, it can cause mild mental disorders such as depression and anxiety disorders. Urban stress is not only caused by a person's personal condition but can also be caused by cities that are not supported by facilities and infrastructure for psychological comfort in urban areas.Therefore, the project "Dialectic Healing Space – Ruang Kesadaran Dialektik" seeks to create a space that becomes a place for therapy to various urban fatigue and busyness. A space that can be an emotional expression for those who experience stress. This design proposes is as a recreational space in the form of a spatial experience that can influence the senses and emotions of visitors through various dialectical media dedicated to achieving the healing process as a form of positive response to help reduce stress levels in the metropolitan by approaching the five senses, physical and psychological interactions of visitors. Keyword: dense city activity; metropolitan; psychological; recreational space; stress ABSTRAKHidup ditengah hiruk piruknya modernisasi perkotaan, gaya hidup yang tinggi, kondisi lingkungan yang padat, dan tuntutan pekerjaan membuat orang merasakan tekanan secara psikologis hingga semakin bertambahnya risiko stres terhadap masyarakat perkotaan. Selain itu, kemajuan teknologi yang pesat menyebabkan masyarakat metropolitan lebih mudah mendapatkan stressor (situasi penuh tekanan). Hal ini menyebabkan semakin sulitnya individu untuk menghadapi stres karena tuntutan sosial, ekonomi, dan lingkungan yang terus mempengaruhi di sekitar kita. Apabila mengalami stres berkepanjangan dapat mengakibatkan gangguan jiwa ringan seperti depresi dan gangguan kecemasan. Stres perkotaan tidak hanya disebabkan oleh kondisi personal seseorang namun juga dapat disebabkan oleh perkotaan yang tidak didukung dengan sarana dan prasarana untuk kenyamanan psikologis di perkotaan. Oleh sebab itu, proyek “Dialectic Healing Space – Ruang Kesadaran Dialektik” ini berusaha untuk mewujudkan ruang yang menjadi tempat untuk “terapi” dari berbagai kepenatan dan kesibukan perkotaan. Ruang yang dapat menjadi pengekspresian emosi bagi mereka yang mengalami stres. Desain ini mengusulkan wadah rekreasi berupa pengalaman ruang yang dapat mempengaruhi panca indera dan emosi pengunjung melalui berbagai media dialektik yang didedikasikan untuk mencapai proses healing sebagai bentuk dari respon positif membantu mengurangi tingkat stres pada masyarakat metropolitan dengan melakukan pendekatan melalui panca indera, interaksi fisik dan psikologis pengunjung. Rancangan menggunakan pendekatan melalui metode biophilic design.